1991
DOI: 10.1346/ccmn.1991.0390108
|View full text |Cite
|
Sign up to set email alerts
|

Diagenetic Structural Transformations in North Sea Jurassic Illite/Smectite

Abstract: Abstract--The Kimmeridgian-Volgian(-Ryazanian) claystone is the principal oil source rock in the troughs of the North Sea. Randomly (R0) ordered mixed-layer illite/smectite (US) appears to have transformed to RI-(IS) or R3-(ISII) ordered simultaneously with oil generation. The proportion of illite layers in I/S increased to 95% d,aring diagenesis in these claystones. Exceptions are three samples of I/S of probably bentonitic origin; these have apparently changed during diagenesis to R0-0rdered I/S containing 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 42 publications
4
18
0
1
Order By: Relevance
“…The R ---0 to R = 1 transition in Ponza I-S occurs relatively abruptly at --45% I (Figure 4), which is consistent with a DC mechanism. The R = 0 to R = 1 transition at Ponza contrasts with a more gradual R = 0 to R = 1 transition at 65% I as observed in shale (Bethke et al, 1986) and bentonite (Inoue et al, 1990), where an SST mechanism was proposed (Inoue et al, 1990;Lindgreen et aL, 1991). The progressive changes in cation ordering ( Figure 7A), layer charge ( Figure 8D), and isotopic composition which also occur over this interval are explained by the transformation of turbostratic, cv, anhedral plates to tv(?…”
Section: Mechanism Of Smectite Iuitization On Ponzamentioning
confidence: 81%
See 2 more Smart Citations
“…The R ---0 to R = 1 transition in Ponza I-S occurs relatively abruptly at --45% I (Figure 4), which is consistent with a DC mechanism. The R = 0 to R = 1 transition at Ponza contrasts with a more gradual R = 0 to R = 1 transition at 65% I as observed in shale (Bethke et al, 1986) and bentonite (Inoue et al, 1990), where an SST mechanism was proposed (Inoue et al, 1990;Lindgreen et aL, 1991). The progressive changes in cation ordering ( Figure 7A), layer charge ( Figure 8D), and isotopic composition which also occur over this interval are explained by the transformation of turbostratic, cv, anhedral plates to tv(?…”
Section: Mechanism Of Smectite Iuitization On Ponzamentioning
confidence: 81%
“…Pollard (1971) proposed a mechanism where A1 and Si diffuse through the interlayer, followed by tetrahedral-sheet distortions as A1 replaces Si. Others studies suggest an SST mechanism but do not propose specific models (Hower, 1981;Hunziker et al, 1986;Inoue et al, 1990;Lindgreen et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abercrombie et aL (1994) noted that the rate of illitization is controlled by silica activity, which in turn is controlled by the rate of precipitation of silica. I-S formation parallels that of maturation of organic material (e.g., Lindgreen et al, 1991). Small (1993) showed that the organic acids evolved during early diagenesis can be critical to rates of illitization, through their control on solubility of A1.…”
Section: Comparison Of Illitization Rates In Coeval Bentonites and Shmentioning
confidence: 97%
“…More recently, diagenetic changes in finegrained sediments have been documented, most strikingly in the case of mixed-layer I/S, at the single crystal structure or clay package scale by transmission/ analytical electron microscopy (Ahn and Peacor 1986;Yau et al 1987;Freed and Peacor 1992) or nuclear magnetic resonance spectroscopy (Lindgreen et al 1991;Schroeder 1993). Differences in shale mineralogy or clay mineral composition either downhole or within a given stratigraphic unit commonly are interpreted as indicating that a diagenetic reaction has taken place.…”
Section: Background and Approachmentioning
confidence: 99%